Sport product dimensions - the impact on purchase behaviour: a case study of physical and health education students / Aideed Ezani Azman - Azman, Aideed Ezani (Faculty of Education, 2014)
Sport product dimensions play role in influencing purchase behaviour. However, it has no clear knowledge on how these dimensions influence students. Thus, this study explores the relationship between the dimensions sport product towards purchase behaviour among PHE students of FOE. Moreover, this study investigates the most influential sport product's dimension that affects purchase behaviour among PHE students of FOE. Quantitative analysis of data obtained through questionnaires based on a model designed by Wong, et al (2007). Questionnaires were distributed to 200 of PHE students of FOE in UiTM Campus Section 17. Reliability analysis test (Cronbach Alpha), descriptive statistic as well as regression test were used to analyze the data. This study revealed that there is a relationship between Sport Product Dimensions and Purchase Behaviour. Moreover, this study found out that cost is the strongest attribute that influences purchase behaviour. This study contribute knowledge and benefit for both sport product's designer/manufacturer with needs and wants of the purchaser so that they can influence customers' purchase behaviour by properly designing their product which can improve their marketing strategies.